In Vitro Cytotoxic Activity of Isostichopus badionotus, a Sea Cucumber from Yucatan Peninsula Coast - Aida R. Pérez-Espadas,; María J. Verde-Star,; Catalina Rivas-Morales,; Azucena Oranday-Cárdenas,; María E. Morales-Rubio,; Lorena V. León-Deniz,; Jaqueline Canul-Canché ,; Leovigildo Quijano, (Journal of Pharmacy and Nutrition Sciences, 2014)
The in vitro cytotoxic activity of hexane, ethyl acetate and butanol extracts of the sea-cucumber Isostichopus badionotus (Holothuroidea) was tested against normal cells (Vero), human cervical carcinoma (HeLa) and breast adenocarcinoma (MCF-7 and MDA-MB-231) ATCC cells by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay. Hexane extracts from body walls and viscera showed high cytotoxic activity against HeLa cells (IC50’s = 48.5 and 42.5 µg mL-1, respectively), while the ethyl acetate extract of body walls was considered low active (IC50 = 98.3 μg mL-1). In addition, the body walls hexane extract showed a good selectivity index value of 12.0.